A novel single-phase white light emitting phosphor Ca9La(PO4)5(SiO4)F2:Dy3+: synthesis, crystal structure and luminescence properties. Issue 29 (3rd March 2016) - Liu, Haikun; Liao, Libing; Molokeev, Maxim S.; Guo, Qingfeng; Zhang, Yuanyuan; Mei, Lefu
Abstract : A novel single-phase white light emitting phosphor Ca9 La(PO4 )5 (SiO4 )F2 :Dy 3+ was prepared through traditional high-temperature solid state technology. Abstract : A novel single-phase white light emitting phosphor Ca9 La(PO4 )5 (SiO4 )F2 :Dy 3+ was prepared through traditional high-temperature solid state technology. The crystal structures of Ca9 La(PO4 )5 (SiO4 )F2 with or without Dy 3+ ions were refined by the Rietveld method. The diffuse reflection spectra, excitation spectra, emission spectra, and decay times were characterized to investigate the photoluminescence properties for application in white light-emitting diodes. The results showed that the Ca9 La(PO4 )5 (SiO4 )F2 :Dy 3+ phosphor could efficiently assimilate n-UV light and emit blue (∼485 nm) and yellow light (∼580 nm), originating from the f–f transitions of Dy 3+ . The critical Dy 3+ quenching concentration (QC) was determined to be about 15 mol%, and the corresponding QC mechanism was verified to be the dipole–dipole interaction. Additionally, the emission colors of all samples were located close to the ideal white light region, and the optimal chromaticity coordinates and correlated color temperature (CCT) were determined to be ( x = 0.338, y = 0.336) and 5262 K. All the above results indicate that the as-prepared Ca9 La(PO4 )5 (SiO4 )F2 :Dy 3+ phosphor could serve as a promising candidate for white-light n-UV-LEDs.